Subdekadische Variabilität des Meereises im atlantischen Sektor - Zimmermann, Robert (2017)
The Arctic sea ice is closely connected to ocean and atmosphere and its spacial coverage reacts sensitively to changes in the climate system. While some influences like the regular seasonal cycle and anthropogenic climate change have been investigated in detail in the past, multiannual variabilities driven by large scale atmospheric oscillations remain less well understood. The here presented work identifies a sub decadal variability in sea ice extent and compares it to atmospheric parameters. Especially the role of the North Atlantic Oscillation (NAO) in shaping this variability is reviewed in detail. Therefore Singular Spectrum Analysis (SSA) was applied to a set of NAO time series varying in length as sea ice data are not yet available on a sufficiently long timescale in order to directly verify a multiannual mode. The resulting mode in NAO Indices is finally found to be coherent with sub decadal sea ice variability in the Atlantic sector of the Arctic Sea.